A remarkable CHF of 345W/cm2 is achieved in a wicked-microchannel using HFE-7100. (15th May 2022) - Li, Wenming; Luo, Kai; Li, Chen; Joshi, Yogendra
Highlights: A new wicked-microchannel is proposed to substantially enhance heat transfer performance of HFE-7100. New silicon wicks can significantly enhance liquid rewetting by increasing capillary-driven force. A significant enhancement of overall HTC, up to 75%, is achieved. A high CHF approximately 345 W/cm 2 is achieved at G = 3465 kg/m 2 s with coolant inlet temperature of ∼20 °C. The mutual enhancements of CHF and HTC are achieved with drastically decreased pressure drops. Abstract: Boiling heat transfer of dielectric fluids is a promising cooling technique for thermal management of microelectronic systems. However, the critical heat flux achievable is generally low, because of the poor thermophysical properties of these fluids. To address this dilemma, we propose a new cooling concept to substantially enhance global liquid supply during phase-change process using enhanced capillary-driven force. Additionally, dedicated vapor pathways are designed among a bank of micro-pillars to facilitate vapor removal. In this work, new wicks comprised of silicon micro-pinfin arrays are explored to significantly enhance the flow boiling heat transfer performance. To examine the functionalities of this wick, experiments on HFE-7100 were carried out with mass velocities varying from 247 to 3, 465 kg/m 2 s. To explore the enhancement mechanisms and to analyze the capillary-assisted flow boiling process, visualization studies were conducted. The results indicate that sustainable evaporation induced by wick microstructures and efficient liquid supply are the enhancement mechanisms compared to parallel microchannels with solid walls. It is found that the overall heat transfer coefficient is substantially increased up to 75%. Remarkably, a high critical heat flux (CHF) of approximately 345 W/cm 2 is recorded at G = 3, 465 kg/m 2 s at coolant inlet temperature of ∼20 °C. Equally importantly, this noticeable enhancement of CHF value is associated with drastically decreased pressure drops compared to microchannels decorated with μ-pinfin fences.